Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America - Cruz, Paulo Vilela; Salles, Frederico Falcão; Hamada, Neusa (Zootaxa, 2017)
Due to historical taxonomic impediments, species of Callibaetis Eaton are difficult to identify. Recent studies have attempted to resolve this problem, although many species still lack complete descriptions; nymphs of several species remain undetermined; and type specimens are lost or poorly known. Given these hindrances, the aim of this study is to review some of the type specimens of Callibaetis from South America. This review provides a series of taxonomic additions and corrections supported by improved morphological evaluations, illustrations and photographs of Callibaetis camposi Navás, C. (Abaetetuba) capixaba Cruz, Salles & Hamada, C. gregarius Navás, C. (C.) guttatus Navás, C. jaffueli Navás, C. (C.) jocosus Navás, C. nigrivenosus Banks, C. (A.) pollens Needham & Murphy, C. (C.) radiatus Navás, C. (A.) sellacki (Weyenbergh), C. stictogaster Navás, C. (C.) viviparus Needham & Murphy, C. (C.) willineri Navás, and C. (C.) zonalis Navás. From among these species, C. stictogaster and C. jaffueli are revalidated; C. nigrivenosus and C. gregarius are designated as nomina dubia; C. (C.) fluminensis Cruz, Salles & Hamada is proposed as a junior subjective synonym of C. (C.) zonalis; and C. gloriosus Navás is proposed as a junior subjective synonym of C. (A.) sellacki (Weyenbergh). Lectotypes are designated for C. camposi, C. jaffueli, C. (C.) radiatus and C. stictogaster.